Circ_0072083 interference enhances growth-inhibiting effects of cisplatin in non-small-cell lung cancer cells via miR-545-3p/CBLL1 axis - Huiping Li; Fangfang Liu; Wenjing Qin (Cancer Cell International, 2020)
Abstract Background Non-small-cell lung cancer (NSCLC) is one of the common cancers in the world. Circular RNA 0072083 (circ_0072083, circZFR) has been reported to be associated with the progression of NSCLC. In this study, we intended to explore the role and the potential mechanism of circ_0072083 in NSCLC. Methods Quantitative real time polymerase chain reaction (qRT-PCR) was performed to detect the expression of circ_0072083, its matching linear RNA (zinc finger RNA binding protein (ZFR)) and microRNA-545-3p (miR-545-3p) in NSCLC cells. The ability of colony formation in NSCLC cells was detected by colony formation assay. The apoptosis and cell cycle were measured by flow cytometry. The metastasis was determined by transwell migration and invasion assays. The protein expression of E-cadherin, N-cadherin, Vimentin and Cbl proto-oncogene like 1 (CBLL1) was examined by western blot assay. The interaction between miR-545-3p and circ_0072083 or CBLL1 was predicted by starBase or Targetscan software. Dual-luciferase reporter assay and RNA immunoprecipitation (RIP) assay were applied to validate these interactions. Nude mice bearing tumors were used to confirm the role of circ_0072083 and cisplatin (DDP) in vivo. Results The level of circ_0072083 was higher in NSCLC tissues and cells relative to that in adjacent non-tumor tissues and normal lung cells. The transfection of si-circ_0072083 inhibited colony formation, cell cycle and metastasis while promoted the apoptosis of NSCLC cells stimulated by DDP. MiR-545-3p was a direct functional target of circ_0072083 in NSCLC cells. CBLL1 could bind to miR-545-3p in NSCLC cells. Circ_0072083 promoted the progression of NSCLC induced by DDP through sponging miR-545-3p and enhancing the enrichment of CBLL1 in vivo and in vitro. Conclusion Circ_0072083 depletion contributed to DDP-triggered inhibition of NSCLC tumor through miR-545-3p/CBLL1 axis.